Analisis Faktor Yang Berhubungan Dengan Konsumsi Sayur Dan Buah Pada Kelompok Wanita Tani (KWT) - Esabilita, Monica; Herawati , Herawati; Istiqamah, Ermina Istiqamah; Kania, Nia; Shadiqi, Muhammad Abdan (Universitas Pahlawan Tuanku Tambusai, 2024)
Low consumption of vegetables and fruit is ranked 10th as a risk factor for death in the world. Around 2.7 million people in the world die every year, the low consumption of vegetables and fruit is related to factors such as knowledge of the availability of vegetables and fruit and support from the Women's Farming Group (KWT). To determine the relationship between knowledge, availability and support from friends in the Women's Farmers Group (KWT) in the work area of ??the South Hulu Sungai Regency Food Security Service. This study used a cross sectional design. The research subjects consisted of 72 people from the Women's Farmers Group (KWT) in the work area of ??the Hulu Sungai Selatan Regency Food Security Service. Data analysis chi square test and multiple logistic regression test. The results of analysis using chi square show the p value of the variables knowledge (p= 0.000), availability (p= 0.001), and friend support (p= 0.008). The results of analysis using multiple logistic regression show the p and Exp B values ??of the knowledge variable (p= 0.011, Exp B= 1.572), the availability variable (p=0.014, Exp B= 1.451), and the friend support variable (p=0.037, Exp B= 1,243). There is a significant relationship between knowledge, availability and support from friends in the Women's Farmers Group (KWT) in the work area of ??the Hulu Sungai Selatan District Food Security Service. The most dominant variable is knowledge.